Disease Control in Age Structure Population. (22nd October 2012) - Kouokam, Etienne; Zucker, Jean-Daniel; Fondjo, Franklin; Choisy, Marc
Abstract : We combine the Leslie model and its derivatives with the classical compartmental SIRS models to build a model of transmission of infected diseases, in a population of hosts, whether opened or closed systems. We calculate the basic reproductive rate R 0 . Under certain conditions, when R 0 < 1, there is a disease-free equilibrium that is locally asymptotically stable. In contrast, when R 0 > 1, this equilibrium is unstable. Then, through an example, we show how we can define public health strategies to tackle an endemic. Finally we carry a global sensitivity analysis based on this basic reproduction rate to exhibit the most influential parameters of our model that are applied to influenza.